Party Simplification Model in Indonesia (Strengthening The Presidential System) and The Presidential Election System in the United States: - Lis Firanti Soedjono; Brendon Neese (Focus Journal : Law Review, 2023)
Elections are a process of electing to fill certain political positions, such as presidents, vice presidents, people's representatives at various levels of government, to the simplest or the least of the village heads. From this perspective of Constitutional Law, direct popular vote is conducted within the period of office in an organization of the state. Then speaking of the election inevitably must be placed within the framework of the principle of people's sovereignty, because the election itself is a manifestation of people's participation that is central to the principle of people's sovereignty or democracy. Its means of political participation of the community to participate in determining public policy. To limit the number of political parties, many methods have been used, such as the electoral threshold and parliamentary threshold. However, the various models used have not been fully effective. In this paper the author will share his views regarding the party simplification model in Indonesia with the aim of strengthening the presidential system. This research article will examine how the ideal model is to simplify parties in Indonesia in the general election system in Indonesia. In addition, this research will discuss the presidential election system in the United States